2019
DOI: 10.1093/cid/ciz1063
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hormonal Contraceptives on Cervical T-helper 17 Phenotype and Function in Adolescents: Results from a Randomized, Crossover Study Comparing Long-acting Injectable Norethisterone Oenanthate (NET-EN), Combined Oral Contraceptive Pills, and Combined Contraceptive Vaginal Rings

Abstract: Background Adolescents in sub-Saharan Africa are at risk for HIV infection and unintended pregnancies. Observational studies suggest that injectable hormonal contraceptives (HC) increase HIV risk, although their effects on genital inflammation, particularly HIV-susceptible Th17 cells, are unknown. In a randomized cross-over study, the effect of injectable norethisterone oenanthate (NET-EN), combined contraceptive vaginal rings (CCVR; NuvaRing®), and combined oral contraceptive pills (COCPs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 32 publications
4
17
0
2
Order By: Relevance
“…The effect of CVR use on cervicovaginal cytokines has been assessed in three previous studies, though none differentiated between follicular and luteal phase. [33][34][35] Two studies used SoftCup samples and longitudinal designs 33,34 and found similar results to ours: elevated IL-6 and IL-1β during CVR use (in addition to IFNγ and TNFα, which we did not find). The third study used cervicovaginal lavage samples and a cross-sectional design 35 and the results agreed less well with ours, in particular, their finding that IL-1β was lower in CVR users.…”
Section: Cvr Use Compared To Menstrual Cycle Phasessupporting
confidence: 85%
See 1 more Smart Citation
“…The effect of CVR use on cervicovaginal cytokines has been assessed in three previous studies, though none differentiated between follicular and luteal phase. [33][34][35] Two studies used SoftCup samples and longitudinal designs 33,34 and found similar results to ours: elevated IL-6 and IL-1β during CVR use (in addition to IFNγ and TNFα, which we did not find). The third study used cervicovaginal lavage samples and a cross-sectional design 35 and the results agreed less well with ours, in particular, their finding that IL-1β was lower in CVR users.…”
Section: Cvr Use Compared To Menstrual Cycle Phasessupporting
confidence: 85%
“…The effect of CVR use on cervicovaginal cytokines has been assessed in three previous studies, though none differentiated between follicular and luteal phase 33‐35 . Two studies used SoftCup samples and longitudinal designs 33,34 and found similar results to ours: elevated IL‐6 and IL‐1β during CVR use (in addition to IFN‐γ and TNF‐α, which we did not find).…”
Section: Discussionsupporting
confidence: 70%
“…42 HT has previously been reported to reduce frequencies of Th17 cells in the vagina during bacterial infections by reducing CD207 + Langerhans' cells, which are known to activate Th17 cells. 43 HT also promotes the expansion of iTreg cells, which play a critical role in downregulating immune responses 44 and upregulating the expression of FoxP3, PD-1, and CTLA-4 via ERα-mediated signaling. 45,46 The disadvantage of HT is that while it suppresses lesion growth it is not a viable option for women trying to achieve pregnancy, as HT interferes with ovarian and uterine endometrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were screened, those 18 years or older provided informed consent, while informed assent from the participant and informed consent from a parent or legal guardian were obtained for participants younger than 18 years old. Eligibility criteria are described in detail elsewhere [ 34 ] [Gill, K. et al, An Open-Label, Randomized Crossover Study to Evaluate the Acceptability and Preference for Contraceptive Options in Female Adolescents, 15–19 Years of Age, as a proxy for HIV prevention methods (UChoose), JIAS , under review]. In brief, the eligibility criteria for enrolment for the parent study included either HC naive or willingness to change method, no symptomatic sexually transmitted infections (STIs) within the prior 40 days, no known sensitivity to any of the study products and no intentions of becoming pregnant throughout the study period.…”
Section: Methodsmentioning
confidence: 99%